A escrita performática de João Gilberto Noll - Vidal, Paloma (Teresa, 2010)
The article approaches two novels by João Gilberto Noll, Berkeley em Bellagio (2002) and Lorde (2004), relating their writing to performance art. The correspondence is useful in so far as it is a writing that aspires to abolish the boundaries between literature and life to become an experiment with the body of the own writer. The main character of these novels is the Brazilian writer, without means, that sees in the invitation of foreign institutions the possibility of temporarily warranting his survival. Travelling deflagrates the experiment that will take the I to the limit of its dissolution